Retorting Photocorrosion and Enhanced Charge Carrier Separation at CdSe Nanocapsules by Chemically Synthesized TiO2 Shell for Photocatalytic Hydrogen Fuel Generation - Sudhagar Pitchaimuthu (ChemCatChem, 2020)
Metal chalcogenide‐based semiconductor nanostructures are promising candidate for photocatalytic or photoelectrocatalytic hydrogen generation. In order to protect CdSe from photocorrosion, a layer of TiO 2 wrapped (shell) onto CdSe (core) nanocapsule via the post‐synthesis process. The morphology studies confirm that a thin crystalline TiO 2 shell (3‐8 nm) wrapped in all the three directions onto CdSe core and thickness of the shell can be controlled through modulating titania precursor concentration. The feasibility of pristine CdSe nanocapsules and CdSe@TiO 2 in transforming visible light to hydrogen conversion was tested through photocatalysis reaction. The CdSe@TiO 2 nanocapsules generating a four‐fold high rate of hydrogen gas than pristine CdSe. In order to understand the role of shell@core, we have examined photoelectrochemical and impedance analysis. The CdSe@TiO 2 nanocapsules showed high photoelectric current generation and less charge transfer resistance at electrode/electrolyte interfaces compared to pristine CdSe. These studies endorse that chemically synthesized crystalline TiO 2 shell played a multifunctional role in (a) surface passivation from photocorrosion, (b) promoting photocharge carrier separation via tunneling process between CdSe and TiO 2 interface. As a result, CdSe@TiO 2 nanocapsules showed a high conversion efficiency of 12.9% under visible light irradiation (328 mW.cm ‐2 ) and turn over frequency is 0.05018 s ‐1 . atom ‐1 .